Lesion and sclerotia development in four pulse species when inoculated with different isolates of Sclerotinia sclerotiorum - Lamont, Grace Elizabeth; Bennett, Sarita (2019)
The fungal pathogen Sclerotinia sclerotiorum has the potential to affect pulse crops as well as canola. Pulse crops are important break crops in cereal cropping systems, but rotations may need to be managed when canola is included in the rotation, as sclerotia, the hard melanised survival structures of S. sclerotiorum, can last up to seven years in soil. This research sought to determine the susceptibility to, and severity of, Sclerotinia stem rot in narrow-leafed lupin (Lupinus angustifolius), faba bean (Vicia faba), chickpea (Cicer arietinum) and lentil (Lens culinaris). Three different isolates of S. sclerotiorum were inoculated onto plants and lesion length, plant height, pod count, survival and sclerotia count recorded. Lupins were the most susceptible, followed by lentil and then chickpea, with the greatest number of sclerotia recorded. There was a significant difference between species and between isolates. Faba beans were the most tolerant and no sclerotia formed within faba bean stems. Isolate CU10.12 was least virulent, causing the smallest yield penalty (pod count), the shortest lesions, no sclerotia, and no plant deaths. Isolate CU8.20 was the most virulent in all these measures. The isolate of S. sclerotiorum as well as the pulse in the rotation is therefore important when determining potential disease severity and future inoculum contribution when including pulses in the rotation.